Determination of Aflatoxin and Ochratoxin in poultry feed ingredients and finished feed in humid semi-tropical environment - Fareed, Ghulam; Anjum, Muhammad Ashraf; Ahmed, Naveed (Journal of Advanced Veterinary and Animal Research, 2014)
A total of 186 samples comprising of poultry feed ingredients (n=114) and finished poultry feeds (n=72) were analyzed for the detection of total aflatoxin (TA) and ochratoxin A (OTA). The concentrations of TA and OTA in the samples were determined using direct competitive Enzyme-Linked Immunosorbent Assay (ELISA). Overall incidence of TA was recorded as 80.64% (n=150/186); whereas, in the feed ingredients, it was 86.84% (n=99/114), and in the finished feeds, the incidence of TA was 70.83% (n=51/72). Corn, cotton seed meal, sunflower meal, and cotton gluten meal were found to be highly (100%) contaminated with TA. The OTA was determined in 63.15% (n=72/114) and 29.17% (n=21/72) feed ingredients, and finished feed samples, respectively, with an overall incidence of 50% (n=93/186). Maximum level of OTA contamination (100%) was recorded in corn gluten meal. However, no feed contained OTA above the acceptable level as set by the European Union on OTA contamination in poultry finished feed. On the other hand, a number of samples contained TA above the acceptable limit. Thus, immediate control measures should be taken to ensure safe poultry for human consumption. http://dx.doi.org/10.5455/javar.2014.a38